Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1371/journal.pone.0270481
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal recombination genomic signatures in the symbiotic arbuscular mycorrhizal fungi Rhizophagus irregularis

Abstract: Arbuscular mycorrhizal fungi (AMF) are part of the most widespread fungal-plant symbiosis. They colonize at least 80% of plant species, promote plant growth and plant diversity. These fungi are multinucleated and contain either one or two haploid nuclear genotypes (monokaryon and dikaryon) identified by the alleles at a putative mating-type locus. This taxon has been considered as an ancient asexual scandal because of the lack of observable sexual structures. Despite identification of a putative mating-type lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have proposed mixing of different nuclei, i.e. nucleotypes, as a result of hyphal fusion (Giovannetti, Azzolini, and Citernesi 1999;Bever and Wang 2005), potentially followed by recombination events identified using polymorphic markers (Vandenkoornhuyse, Leyval, and Bonnin 2001;Gandolfi et al 2003) and sequencing data (Chen, Mathieu, et al 2018;Mateus et al 2022), although these predictions are sensitive to filtering and whether repeat regions are included or not (Auxier and Bazzicalupo 2019). In our study, we detected no was not certified by peer review) is the author/funder.…”
Section: Haploid Nuclei Evolve Independently Within Strains Through T...mentioning
confidence: 58%
“…Previous studies have proposed mixing of different nuclei, i.e. nucleotypes, as a result of hyphal fusion (Giovannetti, Azzolini, and Citernesi 1999;Bever and Wang 2005), potentially followed by recombination events identified using polymorphic markers (Vandenkoornhuyse, Leyval, and Bonnin 2001;Gandolfi et al 2003) and sequencing data (Chen, Mathieu, et al 2018;Mateus et al 2022), although these predictions are sensitive to filtering and whether repeat regions are included or not (Auxier and Bazzicalupo 2019). In our study, we detected no was not certified by peer review) is the author/funder.…”
Section: Haploid Nuclei Evolve Independently Within Strains Through T...mentioning
confidence: 58%
“…Much more common are cases such as the basidiomycete fungus Pseudozyma [16] and AMF Glomus [11], where genomes are found to contain complete and seemingly functional complements of core meiotic genes. Presence does not necessarily prove use in meiosis, but evidence for recombination has been found in AMF genera Glomus and Rhizophagus [81, 82].…”
Section: Discussionmentioning
confidence: 99%
“…However, this was questioned by Auxier and Bazzicalupo [22] who suggested that these may be artefacts. A re-analysis of the data from Chen, et al [21] also detected a small number of potential recombination sites between nuclei [23]. Sperschneider, et al [24] conducted similar analyses with phased genome assemblies of dikaryon isolates and could not detect reciprocal recombination between co-existing nuclei.…”
Section: Introductionmentioning
confidence: 97%